2018
DOI: 10.1111/tesg.12315
|View full text |Cite
|
Sign up to set email alerts
|

A Relational Perspective on Everyday Mobility in the Barcelona Metropolitan Region: Individual and Household‐Related Differences in Daily Travel Time

Abstract: The collective dimension of everyday life plays a key role on how daily mobility patterns are drawn, especially considering relationships at the household level. However, previous literature regarding spatiotemporal behaviour has, above all, focused on individual characteristics detached from their immediate social contexts. By adopting a relational perspective this paper aims to explore how the combination of individual and household-related variables can exert different mobilities in a Mediterranean metropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…By using large-scale human-mobility data, this study is one of the first to systematically demonstrate the existence of the SDMB in restaurant visits on the community level. Our results are in line with previous findings demonstrating the wide existence of the SDMB across various domains, such as choice of transportation mode, travel route, travel distance, daily travel-time, sports facility and general destinations in daily life [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, several studies examined the influence of individuals/households sociodemographic factors on travel route and mode [ 22 ], daily travel-time [ 25 ], and travel distance [ 26 ], and found peoples’ travel behaviors differ according to individual characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…By using large-scale human-mobility data, this study is one of the first to systematically demonstrate the existence of the SDMB in restaurant visits on the community level. Our results are in line with previous findings demonstrating the wide existence of the SDMB across various domains, such as choice of transportation mode, travel route, travel distance, daily travel-time, sports facility and general destinations in daily life [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, several studies examined the influence of individuals/households sociodemographic factors on travel route and mode [ 22 ], daily travel-time [ 25 ], and travel distance [ 26 ], and found peoples’ travel behaviors differ according to individual characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previous findings demonstrating the wide existence of the SDMB across various domains, such as choice of transportation mode, travel route, travel distance, daily travel-time, sports facility and general destinations in daily life [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, several studies examined the influence of individuals/households sociodemographic factors on travel route and mode [ 22 ], daily travel-time [ 25 ], and travel distance [ 26 ], and found peoples’ travel behaviors differ according to individual characteristics. In addition, previous studies observed that individuals make intentional choices of sport facilities for physical activity, which often go beyond their residential neighborhood [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding that women walked proportionally less than men to recreational destinations is also noteworthy. This inequality could be again explained by the temporal constraints resulting from an uneven allocation of household responsibilities (Delclòs-Alió & Miralles-Guasch, 2018 ) and also possibly due to concerns related to safety from crime (Van Dyck et al, 2013 ). This result would also be consistent with a recent large-scale study using novel technologies that showed that men took more overall daily steps when not only walking for transportation was considered (Althoff et al, 2017 ), suggesting that some men have large share of walking for work or for recreation.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, movement is the highest among middle‐aged individuals, a group that Camarero and Oliva (2008) call the ‘support generation’, since they must combine their jobs with family responsibilities, such as caring for offspring or older family members. Young people have the lowest agency over their movement since much of their daily structure is determined by their family (Skelton, 2013), although they spend the largest amount of time on their daily trips (Delclòs‐Alió & Miralles‐Guasch, 2018; Delclòs‐Alió & Miralles‐Guasch, 2019).…”
Section: Introductionmentioning
confidence: 99%